Prognostic assessment of early-stage liver cirrhosis induced by HCV using an integrated model of CX3CR1-associated immune infiltration genes - Haozheng Cai; Jing Zhang; Chuwen Chen; Junyi Shen; Xiaoyun Zhang; Wei Peng; Chuan Li; Haopeng Lv; Tianfu Wen (Scientific Reports)
Abstract Chemokine (C-X3-C motif) Receptor 1 (CX3CR1) primarily mediates the chemotaxis and adhesion of immune cells. However, its role in hepatitis C virus (HCV)-induced early-stage liver cirrhosis remains unexplored. GSE15654 was downloaded from the GEO database. The Cox regression model, CIBERSORT, and LASSO technique were utilized to identify CX3CR1-associated immune infiltration genes (IIGs). Surgical resection samples were collected for verification, including 3 healthy controls (HC), 4 individuals with HCV-induced hepatic cirrhosis, and 3 with HCV-induced liver failure. High CX3CR1 expression correlated with worse prognosis in early-stage cirrhosis. CX3CR1-associated IIGs, namely ACTIN4, CD1E, TMCO1, and WSF1, were identified, showing specific expression in the livers of individuals with post-hepatic cirrhosis and liver failure compared to HC. LOC400499 and MTHFD2 were elevated in individuals with liver failure in comparison to those with hepatocirrhosis. Notably, high infiltration of plasma cells and low infiltration of monocytes were predictive of poor prognosis in early-stage cirrhosis. The combined risk model predicted that high expression of CX3CR1-associated IIGs and increased infiltration of plasma cells were associated with unfavorable prognosis in individuals with HCV-induced early-stage liver cirrhosis. The developed combined risk model effectively predicted the prognosis of these individuals.